LaserCAD III - новая образовательная САПР для изучения полупроводниковых лазеров с квантоворазмерными слоями - Сафонов, И. М.; Петров, С. И.; Овезгельдыев, А. А.; Грищенко , С. В. (УАДО, 2004)
Results of development and application in education of educational CAD system in the area of physical foundations of semiconductor quantum well lasers are presented. Network version and personal version of the CAD system are considered. The ways for modernization and improvement of the software are discussed.
Keywords: образовательная САПР; LaserCAD III